1989
DOI: 10.1017/cbo9780511560880
|View full text |Cite
|
Sign up to set email alerts
|

Literacy and Popular Culture

Abstract: In l750, half the population were unable to sign their names; by l9l4 England, together with a handful of advanced Western countries, had for the first time in history achieved a nominally literate society. This book seeks to understand how and why literacy spread into every corner of English society, and what impact it had on the lives and minds of the common people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
25
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 349 publications
(26 citation statements)
references
References 0 publications
0
25
0
1
Order By: Relevance
“…With regard to those self taught, the reading skill was still dominant (52%), but not to such a great extent, particularly among males (48% could only read). While it is true that the achievements of the pupil were limited by the skills of the instructor (Vincent, 1989), it is impossible to demonstrate with the available data (prison and marriage registers, not to mention autobiographies) that the partial literacy of parents was a correlative for home schooling amongst the working classes. It is conceivable that those parents who had found that the reading skill was both useful and adequate might have been content to pass on that skill to their children but have seen no reason to send their children to school to learn to write, especially where resources were tight.…”
Section: Literate Skillsmentioning
confidence: 98%
See 4 more Smart Citations
“…With regard to those self taught, the reading skill was still dominant (52%), but not to such a great extent, particularly among males (48% could only read). While it is true that the achievements of the pupil were limited by the skills of the instructor (Vincent, 1989), it is impossible to demonstrate with the available data (prison and marriage registers, not to mention autobiographies) that the partial literacy of parents was a correlative for home schooling amongst the working classes. It is conceivable that those parents who had found that the reading skill was both useful and adequate might have been content to pass on that skill to their children but have seen no reason to send their children to school to learn to write, especially where resources were tight.…”
Section: Literate Skillsmentioning
confidence: 98%
“…Vincent has argued that literacy was an increasingly 'common element in the overall [domestic] curriculum as the nineteenth century progressed', though also acknowledges that 'it always had to compete with a wide range of skills which had equal or greater priority' (Vincent, 1989, 56). Vincent and Raey have used nineteenth-century surveys to highlight the substantial presence of books in working-class homes, not only religious texts but also primers and spelling books (Vincent, 1989, Vincent, 1983, Raey, 1991. Most recently, Humphries, on the basis of evidence in working-class autobiographies, declared that a crucial strategy for education was home teaching, and foremost among the domestic instructors were mothers, who were both 'more available' and more ambitious for their children.…”
Section: Literate Skillsmentioning
confidence: 99%
See 3 more Smart Citations